Zasady prawa jako czynnik zapewniający aksjologiczną spójność systemu prawa - Makarucha, Robert (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
A great number of studies about principles of law has been written lately, especially by such contributors as M. Kordela, G. Maroń and S. Tkacz. However, the question is: where does such an interest come from? Principles of law deserve attention because of two major reasons: a judge can develop the law thanks to principles of law and these principles are crucial arguments in legitimization of adjudgements. Principles of law are legal norms with singular characteristics and role. The singular characteristics can be seen in various positions of principles of law, which usually represent the validity of “common” legal norms. However, the singular role provides axiological consistency to the whole system of law. The article consists of three parts. The first one shows that principles of law are an inherent part of the system of law and clarifies what the principles of law are to J. Wróblewski. The second part demonstrates how the principles are determined and explains whether one can talk about the principles of law in the directive and descriptive sense. Moreover, the function of the principles of law in the descriptive sense will be discussed. The principles of law in the directive sense are expressed in regulations; however, these principles in the descriptive sense have to be decoded on the basis of the regulations. The descriptive sense shows if the function of principles of law has the optimizing character, if the principles are “the description” of law and if they can change its content. The third part argues that the principles of law are the prescriptive form of values and their role provides for the axiological consistency of the system of law in the process of its creation, usage and extensive interpretation.
Keywords: spójność aksjologiczna; tworzenie, stosowanie, wykładnia prawa; zasady prawa; zasady prawa w znaczeniu dyrektywalnym i opisowym; postulaty systemu prawa; zasady systemu prawa; opisowy, optymalizacyjny charakter zasad prawa